Current Models for Inpatient and Emergency Room Ophthalmology Consultation in U.S. Residency Programs - Kim, Donna H.; Choi, Dongseok; Hwang, Thomas S. (Journal of Academic Ophthalmology, 2020)
Objective This article examines models of patient care and supervision for hospital-based ophthalmology consultation in teaching institutions.Design This is a cross-sectional survey.Methods An anonymous survey was distributed to residency program directors at 119 Accreditation Council for Graduated Medical Education accredited U.S. ophthalmology programs in the spring of 2018. Survey questions covered consult volume, rotational schedules of staffing providers, methods of supervision (direct vs. indirect), and utilization of consult-dedicated didactics and resident competency assessments.Results Of the 119 program directors, 48 (41%) completed the survey. Programs most frequently reported receiving 4 to 6 consults per day from the emergency department (27, 55.1%) and 4 to 6 consults per day from inpatient services (26, 53.1%). Forty-seven percent of programs reported that postgraduate year one (PGY-1) or PGY-2 residents on a dedicated consult rotation initially evaluate patients. Supervising faculty backgrounds included neuro-ophthalmology, cornea, comprehensive, or a designated chief of service. Staffing responsibility is typically shared by multiple faculty on a daily or weekly rotation. Direct supervision was provided for fewer of emergency room consults (1–30%) than for inpatient consults (71–99%). The majority of programs reported no dedicated didactics for consultation activities (27, 55.1%) or formal assessment for proficiency (33, 67.4%) prior to the initiation of call-related activities without direct supervision. Billing submission for consults was inconsistent and many consults may go financially uncompensated (18, 36.7%).Conclusion The majority of hospital-based ophthalmic consultation at academic centers is provided by a rotating pool of physicians supervising a lower level resident. Few programs validate increased levels of graduated independence using specific assessments.
Keywords: hospital consultation; graduate medical education